CHANGES IN THE QUALITY OF LIFE OF PEOPLE WITH DEMENTIA LIVING IN CARE HOMES - Hoe, Juanita (2009)
Quality of Life (QoL) is now an established outcome measure for people with dementia. There is a need to understand if measures are sensitive to change and what factors are associated with change in QoL in dementia in order to develop interventions to improve QoL and identify who may be most likely to benefit. This study aimed to assess change in QoL in people living in 24 hour care homes using the Quality of Life - Alzheimer’s Disease (QOL-AD) scale and investigated which clinical factors predicted changes in QoL in dementia. We used the QOL-AD scale to rate individual and staff perceptions of residents QoL, for 238 people with dementia, recruited from 24 care homes in the UK. A follow up interview was undertaken at 20 weeks. 192(80.7%) of the 238 residents interviewed at baseline were followed up. A reduction in residents’ QoL was predicted by lower baseline depression and anxiety symptoms, higher baseline QoL ratings, and an increase in depressive symptoms and cognitive deterioration at follow up. While QoL does not necessarily diminish as dementia progresses, it is strongly influenced by the person with dementia’s mood. Improvement in cognition and mood may lead to increased QoL.